Root cultures and elicitation of secondary metabolites from Labisia pumila Benth & Hook. f. var. alata root - Tan, Sin Li (2016)
Labisia pumila var alata (Kacip Fatimah) is currently one of the eighteen main herbs under the EPP 1 of Agriculture cluster of the Economic Transformation Programme,Malaysia. Due to the slow and non-uniform growth of this plant,destructive harvesting and the lack of plant material to sustain the demand of the bio-pharmaceutical industry, an alternative approach is crucially needed to ensure sustainable supply of the herbal raw material. The development of organ cultures such as hairy roots and adventitious roots is a suitable approach to curb the problem of sustaining raw material for the production of pharmaceuticals. Furthermore, the secondary metabolites produced in L.pumila has not been well studied. In this study, hairy roots of L. pumila were successfully established from leaf with petiole explants using three strains of Agrobacterium rhizogenes (A4, NCPPB2629 and NCPPB1855) which produced 16.67%, 70% and 40% transformation efficiencies, respectively.Strain A4 showed a rapid growth rate compared to strain NCPPB2629 and NCPPB1855 with a doubling time of 14 days. Subsequently, liquid cultures were established using strain A4. The presence of rol C gene (strain A4) and rol B (strain NCPPB2629 and NCPPB1855) genes were determined using PCR analysis. Adventitious roots were also successfully initiated using a combination of auxins indole-3-butyric acid (IBA) and α-naphthalene acetic acid (NAA), both supplemented in 2.69 mM concentration in GM1 medium. A total of 100% frequency of adventitious root induction with 9.93 ± 1.18 mean number of roots formed per explant were produced after 14 days of culture. Tandem mass spectrometry platforms [time of flight (TOF) based and quadruple ion-trap based (QTRAP)] were used to detect and compare secondary metabolites produced in different tissues of L. pumila using Principle Component Analysis (PCA). The time-of-flight based tandem mass spectrometer managed to tentatively identify three compounds (FG1, FG2 and AP1) which were produced abundantly in the aqueous extracts of tissue cultured leaves.The production of triterpene saponin, TSrA was also noted in the aqueous extracts of the natural stem (51.33 mg/g), natural roots (132.48 mg/g), tissue cultured leaves (135.65 mg/g), tissue cultured roots (250.75 mg/g) and hairy roots (361.26 mg/g). Methanol extracts of elicited hairy roots in shake flasks using Methyl jasmonate elicitor using different two stage elicitation procedures produced higher concentrations of TSrA (11.8-fold increase in GM3-PM1 media) and AP1 (2.8-fold increase in GM3-PM3 media). Another triterpene saponin, TSrB was also obtained from methanol extracts of hairy roots elicited in GM3-PM2 medium (0.52 mg/g). This compound has never been reported found in any other tissues of L. pumila. Production of hairy root biomass was upscaled further in laboratory scale bioreactors. In terms of biomass production, stirred tank bioreactor with elephant ear impeller, bubbled flask and balloon type bubble bioreactor (BTBB A) produced 6.94-fold, 4.0-fold and 8.42-fold of increase in biomass respectively. The production of hairy root biomass was proven to be effective in BTBB A. Hence, further optimization were made to enhance the production of secondary metabolites. A total of 13 compounds (TSrA, TSrB, TScA, TScB, TScD, TScH, TSmE, TSmH, TSrp, TSdxp, AP1,AP2 and FG1) were detected from various tissues of L. pumila. Among these compounds, TSrB, TScA, TScB, TScD, TScH, TSrp and TSdxp productions were enhanced in the BTBB D bioreactor. This bioreactor produced a maximum biomass accumulation of 15.04 fold. The findings in this study concluded that the supply of herbal raw material can be enhanced through the usage of organ cultures, elicitation and upscaling in bioreactor platforms.